Faktor-Faktor Penyebab Kegagalan Penyedia Jasa pada Proses Evaluasi Penawaran Tender Konstruksi - Virina Revela Putri; Dewantoro; Veronika Happy Puspasari (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2023)
Tender is a series of bidding activity processes that aim to select, obtain, determine, and designate the mostappropriate company to work on a work package. One of them is construction tenders, in which theconstruction industry has a very important role in the economic and social development of a nation. The tenderprocess can be attended by more than one participant, where these companies compete with each other to beable to win a work package. With too many companies, service providers need to have competitive offers inorder to get a positive result in order to win in project tenders. Only the best participant will be the winner inthis competition, so that other participants will be declared failed in the bidding process. This article aims tofind out what factors cause service provider failure in the evaluation process for construction tender bids sothat it becomes a means for self-introspection and finding the best solution that can somewhat minimize thefailure factor. This article uses a literature study method regarding the factors that cause service providerfailure in the process of evaluating construction tender bids by comparing several related journals and basedon current regulations. From the results of the literature study, it was found that there were 45 factors causingthe failure of service providers in the process of evaluating construction bids, which came from 3 previousresearch sources and 2 current regulations.